Implementation of Internet of Things Using Electrocardiogram Sensors to Identify Atrial Fibrillation Heart Disease - Muhammad Ramdan Pamungkas; Wawan Setiawan; Lala Septem Riza (Universitas Pendidikan Indonesia, 2023)
Atrial Fibrillation (AF) is one of the most common heart diseases and increases the risk of stroke and heart failure up to five times. The symptoms of AF are very diverse and often asymptomatic, so an immediate examination is needed to detect it. Given the dangers of AF that could lead to heart failure or death, a diagnosis that can record daily heart rhythms is urgently needed. Research trends show increased use of the Internet of Things (IoT) due to its efficiency and real-time monitoring capabilities. The purpose of this study is to utilize the IoT concept by designing a prototype AF detection device called Atrial Fibrillation Detector (AFD) using a ESP8266 microcontroller device and an AD8266 Electrocardiogram (ECG) sensor. The results of the study show that AFD can identify AF through 4 main stages, including the process of recording ECG data, the process of sending data from the AFD device to the server, the process of processing data to identify the appearance of AF and the process of sending notifications if there is an indication of the appearance of AF. To further test AFD, two experimental scenarios were applied; blackbox testing and comparison of the suitability of AF detection results. In the first experiment, AFD managed to pass the total number of scenarios that existed at 16 scenarios. In the second experiment, AFD only managed to identify exactly 9 out of 15 scenarios.